IMPROVEMENT OF SPEECH CULTURE OF TECHNICAL UNIVERSITY STUDENTS - Larisa F. Belyakova; Tatiana L. Sidorova; Raisa M. Petruneva; Valentina D. Vasilyeva (Высшее образование в России)
The article considers the problem of communicative competence development and speech culture formation of graduates of modern higher education institutions as regards the Russian language. The presented empirical material shows students' typical language and speech mistakes. This paper describes various experience of the Russian language chair, research and methodology council and other subdivisions of university extracurricular activity including student associations aimed at developing students' communicative skills in the field ofRussian speech culture and building linguistic identity.